Pattern and Availability of Basic Amenities in Class-I Cities of Haryana: A Geographical Analysis: Assessing the Pattern and Availability of Basic Amenities in Class-I Cities of Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today India has a large proportion of people residing in urban areas. It is one of the most fast-growing urbanizing countries in the world. It is experiencing an increase in the share of urban population as most urban areas have developed as administrative or service towns. The urbanisation in Haryana as districts to the urbanisation show that there is a large proportion of population residing in urban centre. As per NFHS-III, the offer of population having improved drinking water is just 87 percent in 2015-16 and just 29 percent individuals approach improved sanitation. The NFHS report uncovers that accessibility of drinking water to the general population has improved with the progression of time. In 1993-94 just 62 percent of the family units approached safe drinking water. This extent expanded to 78 percent in 1998-99 lastly 87 percent in 2005-06. As per the report just 24.5 percent of population has funneled water in their residenceplots or yards, and another 17.5 percent rely on open tap points. Cylinder well and bore well considered for 42.8 percent. An attempted may be made here to summaries the major findings of the paper and propose a fee basic amenity with few policy recommendations with regards to financing of the infrastructure and basic amenities in class-I cities of Haryana.